'He Never Liked Sport Anyway' - Mother's Views of Young People Coping With a Bone Tumour in the Lower Limb. (2005) - Earle, Emily A.; Eiser, Christine; Grimer, Robert
Abstract : Purpose: Treatment for a bone tumour can compromise quality of life (QOL), especially for young patients. We used qualitative methods to assess mothers' views of patients' experiences and their coping strategies at approximately 6 months after diagnosis (T1: n =12) and 12–18 months later (T2: n =11). Subjects: Mothers of young people (aged 6–22 years) who were undergoing treatment for either osteosarcoma or Ewing's sarcoma in the lower limb took part. Methods: A semi-structured interview was devised to assess participation in sport, social life, schooling and general mobility. Interviews were transcribed and analysed using content analysis. Results: Mothers reported a number of situations in which QOL was compromised, and these remained relatively constant over time (mean=4.25 at T1 and 4.27 at T2). However, strategies to manage these difficulties changed from Problem (constructive attempts to deal with challenges) to Emotion (managing the situation through use of emotions) focused coping from T1 to T2. Discussion: Although the sample size is small, our results suggest that patients adopt a variety of coping strategies to deal with the physical and social restrictions associated with disease and treatment. The findings suggest that young people continue to experience many stresses up to 18 months after diagnosis. The shift from Problem to Emotion focussed coping over time may suggest a degree of acceptance of practical problems.